It takes a community to conceive: an analysis of the scope, nature and accuracy of online sources of health information for couples trying to conceive. (December 2019) - Kedzior, Sophie G.E.; Bianco-Miotto, Tina; Breen, James; Diener, Kerrilyn R.; Donnelley, Martin; Dunning, Kylie R.; Penno, Megan A.S.; Schjenken, John E.; Sharkey, David J.; Hodyl, Nicolette A.; Fullston, Tod; Gardiner, Maria; et al.
Abstract: This study examined the nature and accuracy of information available across online platforms for couples trying to conceive. A consumer simulation-based investigation of English websites and social media (Facebook, Twitter, Instagram) was undertaken using common search terms identified in a pilot study. Claims about fertility and pregnancy health were then extracted from the results and analysed thematically. The accuracy of each claim was assessed independently by six fertility and conception experts, rated on a scale of 1 (not factual) to 4 (highly factual), with scores collated to produce a median rating. Claims with a median score < 3 were classified as inaccurate. The use of the terms 'trying to conceive' and '#TTC' were common identifiers on online platforms. Claims were extracted predominantly from websites ( n = 89) rather than social media, with Twitter and Instagram comprising commercial elements and Facebook focused on community-based support. Thematic analysis revealed three major themes among the claims across all platforms: conception behaviour and monitoring, lifestyle and exposures, and medical. Fact-checking by the experts revealed that 40% of the information assessed was inaccurate, and that inaccuracies were more likely to be present in the conception behaviour and monitoring advice, the topics most amenable to modification. Since online information is a readily accessible and commonly utilized resource, there is opportunity for improved dissemination of evidence-based material to reach interested couples. Further cross-disciplinary and consumer-based research, such as a user survey, is required to understand how best to provide the 'trying to conceive' community with accurate information.